تأثير برنامج التعليم المبرمج بالأسلوب المتشعب في تحسين مستوى أداء بعض الحركات الارضية في الجمناستك الفني لطالبات - عثمان, م.د دلخواز حميد (Sulaimani Journal for Humanities, 2024)
The research aimed to identify the effect of the educational programmes using the branching method in improving the level of performance of the Kartell skills and roll forwards in artistic Gymnastic for female students. They then searched for an experimental model to suit the nature of the research, and the research was coordinated into two groups with (8) students for each group, an experimental approach with a dual design was used using pre-post measurement for two equal groups, one of which was control and the other was experimental. Equivalence was conducted for two groups in the variables (age, height, weight, some elements of physical fitness, Kartell skills, and roll forwards the researcher used the questionnaire, tests, and scales as means of collecting information, then developed two educational programs. The first included the educational program according to the curriculum prescribed for the second stage students, and the second program included the same program with the addition of programmed instruction the divergent method Proposed to improve the level of performance of some gymnastics skills. Each program consists of (4) weeks, (3) units per week, and the duration of each unit is (90) minutes. The researcher used (arithmetic mean, standard deviation, average ranks, and chi-square) as statistical methods to process the data, and the researcher concluded that the proposed program for learning Sam skills The most important results indicated that the proposed program for learning the skills of the Kartell skills and roll forwards is more effective than the program followed (for the control group) in improving the level of skill performance for the two skills under research in gymnastics for female students at the college.
Keywords: the divergent method; Skill performance Gymnastic floor movements